INTEGRATING ONLINE BLOG IN TEACHING ENGLISH CREATIVE WRITING - Samudu, Mariani; Nirmalasari, Nirmalasari; Arman, Arman (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
This research was set out to examine students’ writing abilities in teaching creative writing subject and investigate the students’ perception in utilizing online blog as a teaching media and how do the online blog influence them in their creative writing subject? Thirty-one fourth semester students of the English Literature study program in the Humanities Faculty, Halu Oleo University who took creative writing subject in the academic year 2020/2021 participated in the research. Data were obtained from students’ results of pre- and post-test on the five components of writing composition, namely content, organization, vocabulary, language use (grammar), and mechanics. The researcher used mix methods to analyze the data both quantitatively and qualitatively. The researcher runs a paired sample t-test with 2 tailed t-tests using the SPSS 16 to test the proposed hypothesis. To reveal students’ perception, descriptive data were transformed into words. Analysis of the data obtained resulted in the followings: pre-test score (M=76.38; SD = 8.77), post-test score (M=86.29; SD=7.78), Df= 30, t-tabel = 1,697 and t-test = 10.686. These results indicated a significant difference on students’ abilities in creative writing subject before and after treatment. Furthermore, students’ perception on the use of online blog is positively related with the students’ achievement. It can therefore be concluded that utilizing online blog as a medium for teaching creative writing is very effective not only in enhancing student’s writing ability in creative writing subject, but also in creating a positive learning environment.